The utility of the Children’s Sleep Habits Questionnaire: Associations between parental report and an objective measure of sleep behavior. - Duraccio, Kara M.; Carbine, Kaylie A.; Barnett, Kimberly A.; Stevens, Kimberly S.; Jensen, Chad D. (Children's Health Care)
We examined associations between the Children’s Sleep Habits Questionnaire (CSHQ) and sleep parameters assessed via actigraphy in a community sample of 111 children. Hypothesized correlations between CSHQ subscales and actigraphy data were not statistically significant, except for the association between CSHQ daytime sleepiness and actigraphy minutes asleep (r = −0.25, p < 0.05). Children with CSHQ scores above the clinical cutoff demonstrated more significant sleep problems, as assessed by actigraphy. Our findings suggest that while the CSHQ may not be as accurate for assessing specific sleep parameters (e.g., sleep duration), it provides a useful indicator of whether children are at risk for sleep problems in general and whether they experience daytime sleepiness.